Pengaruh Insentif dan Motivasi Terhadap Kinerja Karyawan pada PT. Aditama Bogor - Graha Yudha Andarano Putra Pratama (LPPM-STPI, 2021)
This study aims to determine the effect of incentives and motivation partially and simultaneously on employee performance at PT.Aditama Bogor. The approach used in this research is quantitative research and the strategy used in this research is the associative strategy. The research method that will be used is descriptive analysis method using regression analysis, namely to determine how much the contribution / effect of incentives and motivation on employee performance at PT.Aditama Bogor. In this study, data processing was carried out using SPSS ver. 24.00. The population in this study were employees of PT.Aditama Bogor, amounting to 315 employees. The sample used is based on the Slovin formula as many as 76 employees at PT.Aditama Bogor. Based on the analysis and discussion, it shows that incentives have a significant positive effect on employee performance at PT.Aditama Bogor, it can be seen that the significant value of 0.000 <0.05, the first hypothesis (H1) is accepted; Motivation has a significant positive effect on employee performance at PT.Aditama Bogor, it can be seen that a significant value of 0.004 <0.05, the second hypothesis (H2) is accepted and simultaneously incentives and motivation have a significant positive effect on employee performance at PT. Aditama Bogor with a significant value of 0.000 <0.05, the third hypothesis (H3) is accepted.